Patient And Partner Satisfaction Following Penile Prosthesis Implantation (Journal of Pharmaceutical Negative Results, 2023)
Background Erectile dysfunction (ED) is defined as the inability to achieve or maintain an erection sufficient for satisfactory sexual performance. According to the European Association of Urology Guidelines on male sexual dysfunction, penile prosthesis implantation (PPI) is the third-line option for treatment of ED. AIM to assess patient and partner satisfaction after implantation of penile prosthesis and effect of comorbidities on the level of satisfaction. Patients and Methods This was a prospective interventional (non-experimental) follow up study of patients who underwent PPI at our unit in the department of Urology, Faculty of Medicine, Beni-Suef University. The study started from March 2020 till March 2022. Results The mean ages for the men and their spouses were 45.4±8.4 and 29.2±4.6 years, respectively. Level of satisfaction for men and women after 3 months was 80% and 90% respectively. Conclusion PPI produce different levels of satisfaction and is not affected by different comorbidities affecting patients, finally, further studies are necessary to confirm or defy our results. Extended studies are also needed to assess whether longer periods could have different effects on satisfaction in patients and their partners.